Do specialization benefits outweigh concentration risks in credit portfolios of German banks? - Rolf Böve; Klaus Düllmann; Andreas Pfingsten (Deutsche Bundesbank, 2010)
Lending specialization on certain industry sectors can have opposing effects on monitoring (including screening) abilities and on the sectoral concentration risk of a credit portfolio. In this paper, we examine in the first part if monitoring abilities of German cooperative banks and savings banks increase with their specialization on certain industry sectors. We observe that sectoral specialization generally entails better monitoring quality, particularly in the case of the cooperative banks. In the second part we measure the overall effect of better monitoring and the associated higher sectoral credit concentrations on the credit risk of the portfolio. Our empirical results suggest that specialization benefits overcompensate the impact of higher credit concentrations in the case of the cooperative banks. For savings banks, the results on the net effect depend on how specialization is measured. If specialization is gauged by Hirschman Herfindahl indices, the net effect is an increase of portfolio risk due to the higher sectoral concentration. If specialization is instead measured by distance measures, portfolio risk decreases as the impact of better monitoring abilities prevails.
Keywords: G11; G21; 330; bank lending; loan portfolio; diversification; expected loss; savings banks; cooperative banks; concentration; economic capital; credit risk; Kreditgeschäft; Arbeitsteilung; Kreditwürdigkeit; Hausbank; Kreditrisiko; Portfolio-Management; Sparkasse; Kreditgenossenschaft; Schätzung; Deutschland